The development of rainfall temporal pattern in Gambang - Nursyafiqah Amira, Ahmad Zaimi (2019)
The purpose of designing rainfall temporal patterns is to represent the typical variation of rainfall intensities during a typical rainfall. This study focuses on developing a temporal rainfall pattern for the Gambang area in Pahang region. The existing data of rainfall temporal pattern design is not consistence for every year because of Malaysia climate always change and the data of rainfall station nearest district area are used to design the area that is not stated in Malaysia Urban Storm Management Manual Second Edition (MSMA 2). The rainfall temporal pattern will provide rainfall distribution for the specific station area compared to the regional pattern provided in the MSMA 2. The rainfall temporal pattern were developed using Average Variability Method (AVM) and Huff Time Distribution Method (HTDM). This study was conducted in UMP Gambang station and JKR Gambang station which is developing rainfall temporal pattern for several duration of rainfall event. Data of every 5 minutes rainfall event for 15 years starting from 2003 to 2018 were collected from Department of Irrigation and Drainage (DID) for JKR Gambang station and 2016-2018 rainfall data from rainfall station in UMP Gambang. The temporal rainfall pattern developed are for 15 minutes, 20 minutes, 25 minutes, 30 minutes, 45 minutes, 60 minutes, 90 minutes, 120 minutes, 135 minutes, 150 minutes, and 180 minutes. The rainfall temporal pattern were divided the type of temporal pattern according to representative rainstorm pattern classified which is advance-type, intermediate-type and delayed-type. The analysis is run for both method and compare in term of percentage. There was a difference analysis of the rainfall temporal pattern developed by AVM and HTDM method, the difference percentage in each of method from about 28% to 100% for 60 minutes rainfall event. For 120 minutes rainfall event is 46% to 400% while for 180 minutes is about 99% to 100%.